2019
DOI: 10.3390/rs11202370
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid OSVM-OCNN Method for Crop Classification from Fine Spatial Resolution Remotely Sensed Imagery

Abstract: Accurate information on crop distribution is of great importance for a range of applications including crop yield estimation, greenhouse gas emission measurement and management policy formulation. Fine spatial resolution (FSR) remotely sensed imagery provides new opportunities for crop mapping at a detailed level. However, crop classification from FSR imagery is known to be challenging due to the great intra-class variability and low inter-class disparity in the data. In this research, a novel hybrid method (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…CNN-Polygon also resulted in the highest performance when the sample size was less than 200 for Gwangju. This implies that the graph-based CNNs can yield successful classification results with a small training sample size, unlike recent CNN-based land cover classification studies that used large datasets with hundreds to thousands of training samples per class [18,19,31,36,64]. As the sample size increased, the performance of matrix-based models (i.e., CNN-Matrix and CNN-1D) increased to similar or slightly higher levels than the graph image-based models.…”
Section: Model Type Sample Size and Performancementioning
confidence: 96%
See 2 more Smart Citations
“…CNN-Polygon also resulted in the highest performance when the sample size was less than 200 for Gwangju. This implies that the graph-based CNNs can yield successful classification results with a small training sample size, unlike recent CNN-based land cover classification studies that used large datasets with hundreds to thousands of training samples per class [18,19,31,36,64]. As the sample size increased, the performance of matrix-based models (i.e., CNN-Matrix and CNN-1D) increased to similar or slightly higher levels than the graph image-based models.…”
Section: Model Type Sample Size and Performancementioning
confidence: 96%
“…Various CNN architectures have been developed and utilized, including fully convolutional network [20][21][22][23][24][25], U-Net [26,27], modified U-Net [28], and TreeUNet [29]. CNNs have also integrated with other algorithms, such as multilayer perceptrons [30] and support vector machines [31]. Many studies have reported that CNNs have contributed to an accuracy improvement of land cover classification, with the overall accuracy ranging from 81% to 93%, depending on the sensor type, spatial resolution of input images, and target classes [18,19,21,27,[29][30][31][32][33].Feature engineering is defined as the process of transforming raw data into features for better representation of the given problem, which can result in an improvement of the model accuracy on unseen data [34].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Multi-spectral satellite images enable classification and recognition of crops, it takes into account the variations in reflectance as a function of the specific yield types [6]. Crop classification discovers applications in checking and planning efficient crop cultivation, soil and water quality studies, and land usage.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its outperformance and robustness, CNN has been widely used in diverse fields such as object recognition, image classification, and speech recognition [7]. In the field of remote sensing, CNN has also been widely used for the accurate classification of crop, urban land use, wetland, and so on [8][9][10][11]. For the classification of hyperspectral remote sensing, CNN-based methods including 1D, 2D, 3D-CNN, multiscale CNN, residual CNN, and object-based CNN have been proposed [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%